Interaction with Ribosomal Proteins Accompanies Stress Induction of the Anticancer Metallodrug BOLD‐100/KP1339 in the Endoplasmic Reticulum. Issue 10 (1st February 2021) - Neuditschko, Benjamin; Legin, Anton A.; Baier, Dina; Schintlmeister, Arno; Reipert, Siegfried; Wagner, Michael; Keppler, Bernhard K.; Berger, Walter; Meier‐Menches, Samuel M.; Gerner, Christopher
Abstract: The ruthenium‐based anticancer agent BOLD‐100/KP1339 has shown promising results in several in vitro and in vivo tumour models as well as in early clinical trials. However, its mode of action remains to be fully elucidated. Recent evidence identified stress induction in the endoplasmic reticulum (ER) and concomitant down‐modulation of HSPA5 (GRP78) as key drug effects. By exploiting the naturally formed adduct between BOLD‐100 and human serum albumin as an immobilization strategy, we were able to perform target‐profiling experiments that revealed the ribosomal proteins RPL10, RPL24, and the transcription factor GTF2I as potential interactors of this ruthenium(III) anticancer agent. Integrating these findings with proteomic profiling and transcriptomic experiments supported ribosomal disturbance and concomitant induction of ER stress. The formation of polyribosomes and ER swelling of treated cancer cells revealed by TEM validated this finding. Thus, the direct interaction of BOLD‐100 with ribosomal proteins seems to accompany ER stress‐induction and modulation of GRP78 in cancer cells. Abstract : Multi‐omics analysis, including affinity proteomics, revealed that the anticancer drug candidate BOLD‐100/KP1339 may target the ribosomal proteins RPL10/RPL24 and GTF2I. Swelling of the endoplasmic reticulum (ER) and the observation of polyribosomes using imaging techniques indicate that BOLD‐100 treatment may not only inhibit proliferation, but also lead to a functional disturbance of the ER.